Preinduction Cervical Ripening with Prostaglandin E2 in Preterm Pregnancies - Aseel Mosa Jabber (University of Thi-Qar Journal, 2019)
Objective: This study evaluates efficacy of prostaglandin E2 (PGE2) for preinduction cervical ripening in preterm pregnancies, and to identify possible predictors of ripening failure. Methods: Two groups of women admitted for induction of labor were included: Group 1 (n=23) with preterm pregnancies and group 2 (n=25), the control group, at term. The primary outcome measure was the result of cervical ripening. Cervical ripening was induced with successive administration of PGE2 vaginal tablets. After successful cervical ripening, augmentation of labor with oxytocin and/or artificial rupture of membranes are used if necessary. Results: Ripening failure rate was higher in preterm group but not statistically significant (p=0.237). The overall caesarean section rate and the rate of caesarean section due to induction failure were significantly higher in preterm group than in term group. Ripening failure was inversely related to gestational age (p=0.008) even in the preterm group alone (p=0.007). The rate of 5-min Apgar score <7 was comparable in both groups. Conclusion: PGE2 is less effective for cervical ripening at preterm compared to term pregnancies. Lower gestational age was the only independent significant predictor of ripening failure.